Fiscal and monetary policy coordination in the WAMZ: Implications for member states' perfromance on the convergence criteria - Abu Bakarr Tarawalie; Momodu Sissoho; Mohamed Conte; Christian R. Ahortor (West African Monetary Institute (WAMI), 2013)
The study investigates the level of coordination between the fiscal and monetary authorities in the WAMZ countries and its implications for the attainment of the inflation and fiscal deficit criteria. To achieve this objective, the study utilizes the Set Theoretic Approach (STA) and the vector autoregressive (VAR) modeling to estimate the degree of policy coordination in the Zone. The empirical analysis uses annual data for the period 1980 - 2011. Under the STA, coordination exists when shocks to policy goals elicit prudent policy responses. In the case of the VAR, the strength of coordination is measured by the impulse responses of fiscal and monetary policy variables to innovations in inflation, output gap and exchange rate. The results reveal weak policy coordination in all the WAMZ countries during the period, contributing to the non-compliance with respect to inflation and fiscal deficit criteria. The results of the set theoretic models show that explicit policy coordination scores in the WAMZ countries are less than 50.0 percent, with The Gambia obtaining a coordination score of 46.6 percent, Ghana (34.5), Guinea (31.8), Liberia (37.9), Nigeria (46.6) and Sierra Leone (41.3). Additionally, the monetary authorities in the WAMZ countries tend to implement relatively more prudent policies than the fiscal authorities, except in the case of Guinea, where the two policies are at par in terms of prudence. The results of the impulse response also indicate that there is weak response to shocks induced by different variables. It takes a long period for the variables to convergence to their long-run equilibrium path. The key recommendation is that WAMZ countries should strengthen policy coordination by putting in place formal coordination platforms and institutional arrangements for timely and adequate statistics, binding commitments and effective monitoring and evaluation of policy outcomes.
Keywords: 330; coordination; fiscal policy; monetary policy; WAMZ countries; set theoretic approach; VAR